2015
DOI: 10.1007/s10681-015-1363-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined biotic and abiotic stress resistance in tomato

Abstract: Abiotic and biotic stress factors are the major constrains for the realization of crop yield potential. As climate change progresses, the spread and intensity of abiotic as well as biotic stressors is expected to increase, with increased probability of crops being exposed to both types of stress. Shielding crops from combinatorial stress requires a better understanding of the plant's response and its genetic architecture. In this study, we evaluated resistance to salt stress, powdery mildew and to both stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 65 publications
1
76
0
4
Order By: Relevance
“…Moneymaker (MM) were selected on the basis of their salt tolerance and/or powdery mildew resistance (Kissoudis et al , 2015). Additionally, the NILs NIL-Ol-1, NIL-ol-2, and NIL-Ol-4 were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moneymaker (MM) were selected on the basis of their salt tolerance and/or powdery mildew resistance (Kissoudis et al , 2015). Additionally, the NILs NIL-Ol-1, NIL-ol-2, and NIL-Ol-4 were used.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh and dry weights were measured as described previously (Kissoudis et al , 2015). The disease severity was expressed as the disease index (DI) on a scale from 0 to 5, according to Kissoudis et al (2015), assessed at 10, 15, and 25 dpi for the first experiment and at 15 dpi for the second experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of Na + , Cl - , K + , PO 4 3- , SO 4 2- , Mg 2+ , and Ca 2+ was measured with ion chromatography as described previously (Kissoudis et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that PM resistance was negatively affected by 100 mM NaCl (EC level of 10 dS/m) in an introgression line population segregating for partial PM resistance (Kissoudis et al, 2015). Further research indicated that salt stress has the highest impact on disease susceptibility under mild stress conditions (EC∼6 dS/m, 50 mM NaCl), while more severe salinity restored resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Genes can be placed into various of expression cassettes, and subsequently introduced to plants in which they do not naturally occur. Genetically engineered plants can be employed not only as origin of novel cultivars, but can also be helpful in analysing and describing the activity and interplay of gene networks for abiotic stress tolerance (Kissoudis et al 2015). Given the complexity of stress and its genesis, it is rare to meet a single abiotic stress in nature.…”
Section: Introductionmentioning
confidence: 99%